Vaccination against boar taint - effect of restrictive and semi ad libitum feeding regime on production and behavior - Nilsson, Lovisa (2014)
Male piglets have been castrated for centuries to avoid contamination of their meat with boar taint, a strongly unpleasant odour that makes the meat inedible. Today boar taint can be prohib-ited by vaccination against gonadotropin releasing hormone (GnRH) using Improvac®. The aim of this study was to evaluate the efficiency of vaccination on growth performance and behaviour of vaccinated male pigs compared to surgically castrated male pigs. The effect of two feeding regimes, restricted (SLU-norm) and semi ad libitum, was also included in the study. At birth, pigs (n=206) were randomly allocated to the two treatment groups; surgically castrated and vaccination. The study comprised six batches. In batches 1 and 2, vaccination took place 8 and 4 weeks before slaughter and in batches 3-6 10 and 6 weeks before slaughter. Surgical castration was performed before one week of age. The study showed that vaccinated male pigs had a higher growth rate and a lower feed conversion ratio in the interval between first and second vaccination than castrates, irrespective of feeding regime. When fed semi ad libitum, vaccinated pigs had a significantly higher daily weight gain during the total growing/finishing period than castrates (1083 vs. 1040 g). They also had a higher daily lean meat growth (350 vs. 334 g) and a lower feed conversion ratio (2.58 vs. 2.66 kg/kg) compared to castrates. For re-strictively fed pigs no such effect could be seen. Vaccinated male pigs were more aggressive until they have got their second vaccination, however, sexual behaviour and skin lesion declined to the same level as for castrates already after the first vaccination. The results in this study showed that vaccination against GnRH has the potential to improve growth rate, daily lean meat growth and feed conversion ratio when fed semi ad libitum. Vaccination was also effective in reducing aggressive and sexual behaviour to same levels as for castrates. Restrictive feeding did not improve performance or carcass characteristics of vaccinated compared to castrated male pigs in this study.